The Association between Entrepreneurial Knowledge and Family Environment on Entrepreneurial Interest through Self-Efficacy of Indonesian Youth - Devi Rosniawati; Wira Pramana Putra; Farida Akbarina; Risqy Khoirunnisa’; Ni Nyoman Suarniki (Pinisi Journal of Entrepreneurship Review, 2023)
Entrepreneurship knowledge is an internal ability both in terms of creativity, interest and motivation. Able to analyze solutions to possible business risks and reluctant to be shaken by failure. Business should have value and be useful. The purpose of this research is to analyze the influence of entrepreneurial knowledge, family environment, and interest in entrepreneurial students in building a business/enterprise through self-affection. This research is quantitative research using a data processing approach with a population that focuses on entrepreneurial students from the Faculty of Economics and Business, Universitas Negeri Makassar. In this research, data collection used a questionnaire filling technique which was distributed to students. Meanwhile, the sample collection technique used proportional random sampling technique with a sample size of 100 students from a total of 427 students. The data obtained was then processed using the Path Analysis Pattern. The research results show that both directly and indirectly there is a positive and significant influence of entrepreneurial knowledge and family environment on the entrepreneurial interest of entrepreneurship students at the Faculty of Economics and Business through self-efficacy. Except, there is one hypothesis that is not significant, namely the influence of Entrepreneurial Knowledge on Entrepreneurial Interest.